Prostitute or First Apostle? Critical Feminist Interpretation of John 4: 1-42 Over the Figure of the Samaritan Woman at Jacob's Well - Natar, Asnath Niwa (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2019)
The Bible is indeed written in a patriarchal culture and someone finds it desperate to search for the Bible texts that support equality as it provides insufficient passages of equality between men and women. Nonetheless, to use the feminist perspectives is pivotal in searching for equality in reading the Bible texts. It helps people to learn from the efforts made by women in the Bible in order to get out of their oppression and to not take for granted of their miserable situation. Thus in this paper, the author makes a reinterpretation effort on the text of John 4, 1- 42 which has been interpreted in gender bias. The interpretation uses the historical-critical method with a hermeneutic approach to investigation (suspicion) from a feminist perspective. Hermeneutic investigative approach is an approach that reads the text critically and with assumptions (initial suspicion) about the elements of power relations that exist in the text that are dominative and investigates the text. This new approach can result in a new understanding and appreciation of the figures and actions of the Samaritan woman who has been seen as a prostitute and a sinful woman.